2022-RA-196-ESGO Laparoscopic versus open hysterectomy in type I endometrial cancer, a tertiary referral center experience. (20th October 2022) - Gaballa, Khaled; Refky, Basel; Hamdy, Omar; Abdelkhalek, Mohamed
Abstract : Introduction/Background: Surgery had been considered the cornerstone in the management of endometrial cancer especially in early stages. The use of minimally invasive surgeries in patients with endometrial cancers has been widely adopted worldwide. In this study, we discuss the outcomes of type I endometrial cancer patients who underwent laparoscopic hysterectomy at our center. Methodology: This is a retrospective cohort study on type I endometrial cancer patients who had been surgically treated in Oncology Center Mansoura University (OCMU) in the period from January 2014 till January 2019. The basic epidemiologic and clinicopathologic data were collected, thereafter the patients were arranged into two arms according to the surgical approach used whether open or laparoscopic. The two arms were compared regarding epidemiologic, clinicopathologic criteria, and outcomes (surgical and oncological). Results: Patients were categorized into 2 groups; open surgery group (59 patients) and laparoscopy group (60 patients). There was no significant difference between both groups as regards the epidemiologic and clinicopathologic parameters. There was no statistical difference between the 2 groups in the stage of tumor according to FIGO staging. Operative time was significantly longer in the laparoscopy group in comparison to the open surgery group ( p < 0.0001). No significant difference was found between both groups as regards the type of operation, blood loss. The rate of intraoperative complications was nearly similar in both groups. There was no significant statistical difference between the numbers of lymph node yield in both groups. Conclusion: The results in this study support the use of laparoscopy in early stage type I endometrial cancers without compromising the oncological outcomes regarding the disease free and overall survival. We encourage further prospective multicenter randomized trials to consolidate these results.